Emotion Regulation Questionnaire for Cross-Gender Measurement Invariance in Chinese University Students - Zhang, Ying; Bian, Yufang (Frontiers in Psychology, 2020)
Objectives: Emotion regulation has been extensively studied in various areas of psychology. The Emotion Regulation Questionnaire (ERQ) was developed to assess two specific constructs associated with emotion control—cognitive reappraisal and expression suppression (Gross & John, 2003). The instrument displayed sound psychometric properties; however, to date, inquiry regarding the measure’s characteristics has been limited. This study aims to measure cross-gender invariance (MI, measurement invariance) in Chinese undergraduates using the ERQ. Methods: This study measured the psychometric properties of the ERQ in a sample of 847 Mainland China undergraduates (401 males and 446 females) through confirmatory factor analysis. The tests of MI were used to examine potential structural differences based on gender. Results: The findings supported the measure’s original structure with all demographic groups and demonstrated exceptional fit. Additional normative data for gender and ethnic groups are included as well. The results also supported the use of the instrument in future research. Conclusions: The two-factor structure in the ERQ establishes a cross-gender equivalence between males and females in Chinese college students. This study supports the use of the instrument in future research.